Corpi di reato. Un’archeologia visiva dei fenomeni mafiosi nell’Italia contemporanea - Bonaventura, Tommaso; Imbriaco, Alessandro; Severo, Fabio (Rivista di studi di fotografia. Journal of Studies in Photography, 2017)
For a long time the mafia has been perceived as a scattered, multiform, almost invisible entity. After the 1990s and the height of a sweep of bloodshed, organized crime in Italy slowly changed its appearance and began to blend in with the political and economic fabric of the country. Corpi di reato proposes to contrast this dispersion and restore a tangible sightline of the mafia by retracing the marks it left around the country. It also aims to show the void, the emptiness, that these criminal acts provoked.